Left ventricular remodeling patterns in patients with moderate aortic stenosis. (4th February 2022) - Stassen, J; Ewe, SH; Hirasawa, K; Butcher, SC; Singh, GK; Ammanullah, RA; Ding, ZP; Pio, SM; Chew, NWS; Sia, CH; Kong, WKF; Poh, KK; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): ESC Training Grant App000064741 Background Moderate aortic stenosis (MAS) is associated with an increased risk of adverse events. Although left ventricular (LV) adverse remodeling is associated with worse outcomes in patients with severe AS, the prognostic significance of different patterns of LV remodeling in MAS has not been investigated. Purpose To investigate the association between different patterns of LV remodeling on outcomes in patients with MAS. Methods Patients with MAS (aortic valve area >1.0 and ≤1.5cm2) were stratified into 4 groups according to the pattern of LV remodeling: normal geometry (NG), concentric remodeling (CR), concentric hypertrophy (CH) or eccentric hypertrophy (EH). Clinical outcomes were defined as all-cause mortality and a composite of all-cause mortality and aortic valve replacement (AVR). Results Of 1931 patients (age 73 ± 10 years, 52% men) with MAS, 344 (18%) had NG, 469 (24%) CR, 698 (36%) CH and 420 (22%) EH. Patients with CH were more likely to be female, had more hypertension, were more symptomatic (NYHA ≥III) and had more pronounced LV diastolic dysfunction, whereas patients with EH had more coronary artery disease, were more symptomatic (NYHA ≥III) and had lower LV ejection fraction than patients with NG. Patients with CH had higher aortic mean pressure gradients and peak aortic jet velocities than patients with NG. During a median follow-up of 51 (IQR 25 - 83) months, 833 (43%) patients died. For the composite endpoint, 1286 (67%) patients underwent AVR (n = 613) or died (n = 673) during a median follow-up of 35 (IQR 14 - 60) months. Patients with CH and EH had significantly lower survival rates (p < 0.001; Figure 1) and event-free survival rates (p = 0.004) compared to patients with NG/CR. On multivariable analysis, CH was independently associated with all-cause mortality (HR:1.267; 95% CI:1.024 – 1.568; p = 0.029), whereas both CH (HR:1.293; 95% CI:1.090 – 1.533; p = 0.003) and EH (HR:1.222; 95% CI:1.013 – 1.474; p = 0.036) were associated with the composite endpoint of AVR and all-cause mortality (Figure 2). Conclusions In patients with MAS, different patterns of LV remodeling are observed with CH being independently associated with an increased risk of all-cause mortality. Risk stratification according to the different patterns of LV remodeling may help to identify patients with MAS who are at increased risk of adverse events and may benefit from closer follow-up.